Textual coherence in Surat At-Takwir Through a conscientious referral - A textual study - Al-Saif, Hamad Abdullah Hamad (Journal of Arabic Language Sciences and Literature, 2023)
This research is concerned with the subject of referral by studying the text as having one meaning and being read in one reading. To study the referral in its parts and divisions to show the extent to which the role of referral is shown as an important tool for achieving textual coherence in reading the text as an integrated unit, the beginning of which is connected to the end, and it shows the influence of the text by external factors that helped in the formulation and casting of the text. I have taken Surat At-Takwir as a broad model in the field of application. The referral had a clear impact in this noble surah, in which the textual coherence factors expanded, as the pronoun abounded in it, and the approach adopted in this study was the inductive approach, in which the The particles of the topic and what is related to it follow the issues of textual coherence in Surat Al-Takwir.